Mobile Banking Acceptance: A Modified UTAUT 2 Model with Trust and Risk Integration - Nur Aeni Hidayah; Adam Kusuma Putra; Zainul Arham; Syopiansyah Jaya Putra; Bayu Waspodo (SISTEMASI, 2026)
This study examines the factors influencing the acceptance of the JakOne Mobile mobile banking application developed by Bank DKI using a modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, extended with the external variables of perceived trust and perceived risk. Although the application has a high number of downloads, it faces significant challenges related to user satisfaction. This is reflected in the sharp polarization of ratings, where one-star reviews account for 32.17% of total reviews, indicating fundamental issues in a substantial portion of the user experience. This research employed a quantitative approach, with data collected from 450 respondents in the Jabodetabek region through an online questionnaire. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test 13 proposed hypotheses. The main results show that performance expectancy and facilitating conditions have a positive and significant effect on behavioral intention. Interestingly, this study found that price value, hedonic motivation, and habit have a significant negative effect on behavioral intention. Furthermore, trust was proven to effectively reduce perceived risk, while effort expectancy and social influence showed no significant influence. The practical implications of these findings suggest that Bank DKI should prioritize improving the technical performance of the application and develop communication strategies focused on building user trust, rather than emphasizing low cost or entertainment-related aspects.